Even prohibited, behold for us: the challenge before ecumenical religious manifestations and prohibitions on Brazil history - Ritzmann, Cristiano (Vox Scripturae - Revista Teológica Internacional, 2014)
In societies where there is not religious hegemony, religious plurality appears as a result of democratization recognizing legitimacy in the various religious expressions. Religious pluralism is an inevitable reality that is part of the XXI Century scenario. The presence of religious diversity is increasing worldwide. The fact is that religious pluralism  has currently challenged all religions into dialogue practice. In Brazil this reality is not different. How to get out of an ecumenical stalemate and promote engagement and dialogue between religious manifestations of our country? How to be church in the midst of a society of varied culture and religion? We are called to the dialogue practice and coexistence among the different denominations in order not to fall in the religious fundamentalism.
Keywords: Religion; Pluralism; Ecumenism; Ecumenical dialogue; History; Brazil